Cohesive Polydensified Matrix® hyaluronic acid volumizer injected for cheek augmentation has additional positive effect on nasolabial folds - Gauglitz G; Steckmeier S; Pötschke J; Schwaiger H (Dove Medical Press, 2017)
Gerd Gauglitz,1 Stephanie Steckmeier,1 Julian Pötschke,2 Hannah Schwaiger,1 1Department of Dermatology and Allergy, Ludwig-Maximilian University, Munich, Germany; 2Department of Plastic and Hand Surgery, Klinikum St Georg gGmbH, Leipzig, Germany Purpose: Cohesive Polydensified Matrix® hyaluronic acid (CPM-HA) volumizer has been used successfully for several years to reverse biometric volume loss during facial aging. This observational study explored the additive effect on nasolabial folds when CPM-HA volumizer is injected into the neighboring cheek area.Patients and methods: In this open-label, prospective, postmarketing noninterventional study, 18 adult patients seeking esthetic enhancement of the lateral cheek hollows and cheekbone area were injected with CPM-HA volumizer integrated with lidocaine (CPM-HA-VL) in the upper or lower cheek area. Safety and performance of CPM-HA-VL up to 12 months after injection with follow-up visits at week 4 and month 3, 6, and 12 were assessed. The primary endpoint was improvement of cheek fullness on the validated Merz Aesthetics Scales. Additionally, changes in nasolabial folds were quantified using a phaseshift rapid in vivo measurement of skin optical three-dimensional (3D) in vivo measurement device. Results: Patients (94.4% female, median age 52 years, age range 39–69 years) were injected with a mean volume of 2.5±1.1 mL CPM-HA-VL per side. Immediately after injection, mean severity for upper and lower cheek fullness assessed on the validated MAS improved from 2.5±0.6 and 2.8±0.5, respectively, to 1.0±0.0, and remained unchanged through month 12. Improvement in relation to baseline was attested on the Global Aesthetics Improvement Scale for all assessments. Compared with baseline, the following assessments offered a statistical significance in the reduction of wrinkle depth of nasolabial folds (maximum depth reduction by 30.4% at 3 months) according to optical 3D in vivo measurements. Pain during injection was minimal and abated within 30 minutes. Treatment was well tolerated and led to great patient satisfaction.Conclusion: CPM-HA-VL injected into the upper and lower cheeks led to long-lasting satisfactory cosmetic results in cheek augmentation as well as in reducing depth of nasolabial folds adjacent to the injection site. Keywords: CPM-HA-VL volumizing filler, facial rejuvenation, esthetic procedure, dermal filler, PRIMOS 3D